The Influence of Physical and Non-Physical Work Environment Factors on Employee Satisfaction at PT PLN (Persero) ULP Panakkukang - Damar Kuncara; Samsul Rizal; Muh Nur Rasyid (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study examines the influence of physical and non-physical work environment factors on employee satisfaction at PT PLN (Persero) ULP Panakkukang. Using a quantitative approach, the research employed a saturated sampling technique involving all 79 employees from various divisions. Data were collected through questionnaires that had been tested for validity and reliability, complemented by documentation and observation. Analytical methods included instrument testing, classical assumption tests, multiple linear regression, and hypothesis testing using IBM SPSS 26. The results show that the physical work environment has a regression coefficient of 0.479 with a significance level of 0.00, while the non-physical work environment has a coefficient of 0.232 with a significance level of 0.01. Both variables have a positive and significant effect on employee satisfaction, with an adjusted R² value of 0.674, indicating that 67.4% of employee satisfaction is explained by the two factors studied. The t-test confirmed that both physical and non-physical work environments significantly contribute to satisfaction, suggesting that improvements in workplace conditions—such as facilities, comfort, and supportive interpersonal relationships—can enhance employee well-being and performance. These findings emphasize the strategic role of comprehensive work environment management in maintaining employee motivation and productivity, particularly in service-oriented organizations such as PLN.